LOMATOGONIUM GAURGOPALII, A NEW SPECIES OF GENTIANACEAE FROM SIKKIM HIMALAYA. (26th June 2019) - Midday, M.; Ghosh, J.; Maity, D.
Abstract : Lomatogonium gaurgopalii sp. nov., a new species of Gentianaceae from Sikkim Himalaya, is described and illustrated. It can be distinguished from its morphologically closest relative, Lomatogonium cherukurianum S.K.Dey & D.Maity, mainly by its robust habit, longer internodes, much larger creamy yellow flower and much larger floral parts; the presence of many hairs in an inverted semilunar arrangement behind the filament bases; and its larger, narrowly ovoid to narrowly ellipsoid ovary. Lomatogonium gaurgopalii is also unique in having pollen grains with striate-reticulate exine ornamentation without perforations.